1974
DOI: 10.1021/ja00816a025
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of reactions at carbon-transition metal .sigma. bonds. .pi.-Cyclopentadienyldicarbonyliron erythro-and threo-3,3-dimethylbutyl-1,2-d2

Abstract: Convenient, stereoselective syntheses of threo-and ¡?r>7/iro-3,3-dimethylbutan-l-oI-/,2-i/2 (1) are described. Reaction of the p-bromobenzenesulfonate esters of 1 with CsHsFeCCOjüMgBr, -Li, or -Na yields ircyclopentadienyldicarbonyliron erythro-and ?Areo-3,3-dimethylbutyl-/,2-d2 (erythro-and threo-2) with >95% inversion of configuration at carbon. Bromination of 2 in pentane, chloroform, carbon disulfide, and dimethylformamide, and iodination in carbon disulfide, all take place with >90% inversion of configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(54 citation statements)
references
References 8 publications
3
49
0
2
Order By: Relevance
“…mostly, more crowded systems [1][2][3]. It also agrees with the stereochemistry of the reverse proc ess, carbonyl insertion reactions [5][6][7]. This provides further support for the notion [10] that biological carbonyl insertion reactions, even in sterically unhin dered cases like the formation of an acetyl group by "carbonyl insertion" into a metal-methyl bond, also proceed with retention of configuration.…”
Section: Discussionsupporting
confidence: 75%
“…mostly, more crowded systems [1][2][3]. It also agrees with the stereochemistry of the reverse proc ess, carbonyl insertion reactions [5][6][7]. This provides further support for the notion [10] that biological carbonyl insertion reactions, even in sterically unhin dered cases like the formation of an acetyl group by "carbonyl insertion" into a metal-methyl bond, also proceed with retention of configuration.…”
Section: Discussionsupporting
confidence: 75%
“…First, Fu and co-workers carried out mechanistic experiments of alkyl–alkyl cross-couplings that indicated that the palladium-catalyzed cross-coupling reaction of stereochemically defined alkyl electrophiles proceeds principally with inversion. xxvi Using a strategy pioneered by Whitesides, xxvii Fu and co-workers used the anti -diasteromer of deuterium-labeled primary alkyl tosylate to elucidate the stereochemical outcome of the reaction. As shown in equation 6, alkyl tosylate 40 was subjected to reaction conditions with phenyl-9-borabicyclo[3.3.1]nonane (phenyl-9-BBN) in the presence of catalytic Pd(OAc) 2 to afford 41 in 54% yield and 86% inversion at the carbon bearing the leaving group, corresponding to a syn : anti ratio of 6:1.…”
Section: Stereospecific Reactionsmentioning
confidence: 99%
“…Incorporation of deuterium at the α and β position of primary alkylboranes allows for determination of configuration by analysis of 1 H NMR coupling constants, while introducing little thermodynamic preference for formation of one diastereomer over the other. xxvii The Soderquist and Woerpel groups independently showed that alkylboron reagents undergo palladium-catalyzed cross-coupling reactions with aryl and vinyl halides with retention of configuration (Scheme 22a,b). 73 In a recent report by our laboratory we have demonstrated that the same holds true for nickel-catalyzed cross-coupling reactions with alkyl halides (Scheme 22c).…”
Section: Stereospecific Reactionsmentioning
confidence: 99%
“…Lastly, no experimentally determined Eyring activation parameters or Hammett reaction constants are available for 72,73 This S N 2 reaction, with [Fp] − as the nucleophile and an alkyl halide as the electrophile, would also be expected to exhibit a large and negative ΔS ⧧ as well as a reaction constant of ρ > 1. The Whitesides stereochemical probe did not react with either (IPr)Cu-Fp or (IMes)Cu-Fp, even after long reaction times or under forcing conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%